P729 A 'real-world' retrospective multi-centre study comparing infliximab and adalimumab for the maintenance of remission in ulcerative colitis. (16th January 2018) - Kronsten, V; Colwill, M; Nayeemuddin, S; Limdi, J; Selinger, C; Scott, G; Al-Hillawi, L; Salehi, S; Blaker, P; Chung-Faye, G; Kent, A; Dubois, P; et al.
Abstract: Background: Anti-tumour necrosis factor (TNF) therapy has revolutionised the treatment of ulcerative colitis (UC), particularly in moderate-to-severe disease. However, in the maintenance of remission, though response rates are significantly greater than placebo, these drugs tend to perform less well. Route of administration may influence efficacy and recent network meta-analyses of trial data indicate a superiority of intravenous drugs (IV; Infliximab; IFX) over subcutaneous (SC; adalimumab; ADA). 1 We conducted a retrospective multi-centre case–control study to compare the efficacy of these two drugs. Methods: Patients administered IFX or ADA as their first biologic, identified from the therapy databases of five UK hospitals, were included, only if they had completed induction dosing and entered the maintenance phase. Patients receiving IFX as 'rescue' therapy were excluded. Data were collected and compared for pre-biologic disease activity (Simple Clinical Colitis Activity Index (SCCAI), C-reactive protein and calprotectin) and throughout anti-TNF therapy. The primary end-point for comparison was the number of patients remaining in clinical remission at 52 weeks (combined features of continuing IFX or ADA therapy and SCCAI score ≤3). Data were collected for duration of therapy, or up to last follow-up, if beyond 52 weeks. Results: In total, 63 IFX (40.7 ± 15.4 years, 28F) and 62 ADA (36.4 ± 14.3 years, 28F) patients were analysed. There were no statistically significant differences in demographics or pre-biologic disease activity between the two groups. The median SCCAI at 14 weeks was significantly lower in IFX (2 (0–4)) than ADA (4 (2–8)) ( p = 0.01). At 52 weeks, 46 (73%) IFX patients and 29 (47%) ADA patients remained on therapy ( p = 0.005) and in remission (22 (35%) vs. 5 (8%), p = 0.0006). Primary non response was the reason for treatment cessation in 14 (23%) ADA patients and 4 (6%) IFX patients ( p = 0.02). Conclusions: Our results from a real-world cohort mirror those produced in the network meta-analyses of clinical trials for these agents, suggesting that IFX is superior to ADA in UC maintenance of remission, demonstrated by improvement in SCCAI scores and treatment continuation at 52 weeks. There were no significant differences in colectomy rates, hospital admission for acute flares or adverse events in the study timeframe. References: 1. Danese S, Fiorino G, Peyrin-Biroulet L, et al. Biological agents for moderately to severely active ulcerative colitis: a systematic review and network meta-analysis. Ann Intern Med, 2014;160:704–11.